Coming to blows with the audience - Castellano San Jacinto, Tania (Re-visiones, 2024)
Starting with Dadaism, which strikes the public’s moral standing, and above all with a certain kind of cinema which, according to Walter Benjamin, can punch the spectator awake, this article studies several different kinds of impact that contemporary art exerts. In this context, the possibility of an “acceptable shock” and an “unacceptable shock” is put forward, and, within both of these categories, the effectiveness of coming to blows with the audience is studied from the perspective of various different authors. On the other side of all this is the spectator abused by excess –whose modern antecedent we have situated in Georg Simmel’s blasé figure-, and another who is perhaps shaken up by the world before him, which would imply political mobilisation through art.